The general form of an equation is given by
![(x-a)^2+(x-b)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/j27bbcfyg3w6k583gx6mr9v294cmd8mryt.png)
where (a,b) are the coordinates of the centre and r is the radius of the circle.
Now the coordinates of the centre are the midpoint of the points (2,6) and (8,-6).
The midpoint is calculated as follows
The vertical distance between (2,6) and (8,-6) is
![6-(-6)=12](https://img.qammunity.org/2023/formulas/mathematics/college/hvt845bd4n98e45i4hgqjql7vc1npx2kg4.png)
half of this is 6.
The horizontal distance between (2,6) and (8,-6) is
![2-8=-6](https://img.qammunity.org/2023/formulas/mathematics/college/4hh87ljdrtiv4frg1euhnrzt4yhsjqntr1.png)
half of which is -3.
suntracting y = 6 and x = -3 to (2,6) gives
![(2+3,6-6,)=(5,0)](https://img.qammunity.org/2023/formulas/mathematics/college/6nq15pndunua0xojmpm1tsjqf7ah6ga4w9.png)
Hence, the coordinates of the centre are (a, b ) (5,0).
Now, the radius of the circle is half the distance to the midpoint
![\begin{gathered} r=\sqrt[]{6^2+(-3)^3} \\ r=3\sqrt[]{5} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d5s7s8gi5b9vnw44ebl3qknvaom21fq4zn.png)
Hence, the equation for the circle is
![\begin{gathered} (x-5)^2+y^2=(3\sqrt[]{45}) \\ (x-5)^2+y^2=45 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hdgj4bogru1oook9hhcx5eou84991n9j7x.png)